THREE REASONS TO ADDRESS AI IN EDUCATION NOW - Ilhomjon Madaminovich Tukhtasinov (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
Artificial Intelligence (AI) is rapidly transforming education by offering new opportunities to improve teaching, learning, and administrative processes. Educators increasingly recognize the potential of AI-powered tools such as speech recognition, adaptive learning systems, automated assistants, and generative applications to personalize instruction, support multilingual learners and students with disabilities, enhance lesson planning, and reduce teacher workload. At the same time, the adoption of AI raises substantial concerns regarding data privacy, security, algorithmic bias, transparency, fairness, academic integrity, and the risk of excessive automation in decision-making. Educational stakeholders—including teachers, policymakers, researchers, developers, families, and students—have emphasized the urgency of establishing safeguards and governance frameworks to ensure responsible AI integration. AI systems must be designed to complement rather than replace human educators, preserving professional judgment and pedagogical relationships. This paper highlights the importance of balancing innovation with ethical responsibility by promoting transparency, equitable access, accurate data use, and human oversight. While debates continue over the challenges of AI in education, growing consensus suggests that its benefits can significantly enhance educational outcomes when implemented thoughtfully and responsibly.